Couples' Disease: The Experience of Living with a Partner with Chronic Depression. Issue 2 (3rd April 2018) - Priestley, Jemma; McPherson, Susan; Davies, Fran
ABSTRACT: This study is concerned with the impact of chronic depression on partners. Thirteen male and female participants who lived with a partner with chronic depression were interviewed. Data were analyzed using thematic analysis. Findings highlighted a need for caregivers to be more centrally involved in their partner's care, given that they face stigma, shifts in role identity, and uncertainty, which all potentially threaten the level of support they can give their partner. In this sense, depression might be described as a "couples disease, " suggesting that couples therapy and group support for partners should be more widely available to help reduce the burden on partners and potentially prevent relationship breakdown.